امام فخر الدین رازی بحیثیت صوفی و عارف: تحقیقی مطالعہ (تفسیر ’’مفاتیح الغیب ‘‘ کی روشنی میں): Imam Fakhruddin Razi as Sufi and Arif: An Exploratory Study (In the light of Tafseer "Mufatih al-Ghaib") - Akbar, Dr. Hafiz Muhammad; Mahmood, Dr. Khalid (Al-Amīr Research Journal for Islamic Studies, 2024)
Fakhr al-Din al-Razi was a great Muslim scholar, intellectual, philosopher and theorist. He was born in Iran and died in Afghanistan. He left behind him so many books and publications on various features of Islam. According to some research scholars, when an index of his books was prepared, it consisted of 104 pages. One of Imam Razi’s surprising works is his outstanding interpretations and explanations of the Holy Quran titled Mafaateeh-ul-Ghaib (Keys to the Hidden facts). Later on, this tafsir was known as Tafsir-E-Kabir (Prodigious Tafsir) because it consists of 32 volumes. In this article, the personality of Imam Razi as being Sufi is discussed in the light of his tafsir. After reading the Tafsir, it comes in front of us that there are many evidences and signs that are enough to prove that Imam Razi was very much influenced by sufiism particularly in the last part of his life. It is also noteworthy that he wrote this tafsir after being influenced by Sufiism. For this reason, many references can be provided on this claim that Imam Razi was one of the followers who are on the original Tasawuf derived from Quran and Sunnah. Key Words: Fakhr al-Din al-Razi, Tafsir, Mafaateeh-ul-Ghaib, Tafsir-E-Kabir, Sufiism.